ANALISIS PENGARUH USIA DALAM PEMEROLEHAN BAHASA - Wasis Sirutama (Jurnal Inovasi Penelitian, 2023)
Language acquisition is the process by which humans gain the ability to capture, produce, and use words for understanding and communication. This capacity involves a wide range of abilities, such as syntax, phonetics, and a broad vocabulary. Many factors influence a person. Broadly speaking, these factors are divided into internal and external factors. Personal factors include class activity, attitudes towards teachers and subject matter, and students' learning techniques, while general factors include age, talent, cognitive ability, motivation, and personality. The external factors include the formal environment and the informal environment. One of these several factors affecting second language acquisition is the age factor, which is the focus of this study. As a result, this study was carried out to examine theories about the acquisition of a second language based on age and determine whether they are still relevant today. This type of research is qualitative with a qualitative descriptive method, meaning that the vocabulary is the main data point of this research. According to the research findings, the average age of acquisition of each sample of 5 students, namely elementary school (154 words), junior high school (174 words), and high school (185), indicates that age has an effect on language acquisition, but the difference is not statistically significant. This difference is due to the level of students' knowledge in mastering vocabulary; for example, at the age of 10–11 years or the elementary level, they use more verbs, while at the age of 14, in junior high school, and at the ages of 16–17 years, the high school level uses more nouns, specifically for those aged 16–17 years. There are technical words such as "Felis silvestri," "Felidae," "Cocos nucifera," and "Felis catus." This does not occur between the ages of 10-11 and 14-15.